High growth rates of a dominant calanoid copepod in the northern San Francisco Estuary. (17th December 2019) - Owens, Stephanie; Ignoffo, Toni R; Frantzich, Jared; Slaughter, Anne; Kimmerer, Wim
ABSTRACT: We measured growth rates of the copepod Pseudodiaptomus forbesi in relation to food, environmental conditions and hydrology in the northern San Francisco Estuary, California, USA. We conducted 38 copepod growth-rate experiments during summers 2015–2017 at four sites in a tidal, freshwater channel that had strong gradients in environmental conditions. Copepod growth rates were measured using the artificial cohort method with an image analysis technique, and seston attributes were measured to investigate the effects of food quantity and quality on copepod growth rates. Growth rates ranging from 0.03 to 0.47 day −1 (median 0.30 day −1 ) and growth rates, chlorophyll, turbidity and total lipids in the channel decreased with distance downstream. Growth rates had a saturating response to chlorophyll and were generally higher than rates previously measured in larger estuarine channels, presumably because of higher chlorophyll and temperature in our study area. Growth rate was positively associated with biovolume of cyanobacteria but not with that of other major phytoplankton groups, which is consistent with a recent finding of high feeding of P. forbesi on cyanobacteria. This adds to the small but growing literature suggesting that crustacean planktons are able to overcome the nutritional deficiencies of cyanobacteria to grow and reproduce.